Silk of the Indian meal moth Plodia interpunctella (Hübner, 1813) affects the human colon cancer cells - Nikodijević Danijela; Milutinović Milena; Radenković Nikola; Blagojević Stefan; Vasiljević Anđela; Jurišić Vladimir; Predojević Dragana; Vukajlović Filip; Pešić Snežana (Kragujevac Journal of Science)
The insect silk protects the larvae that produce it. This implies that it may contain biologically active substances that can be used in medicine. In this paper, the cytotoxic and proapoptotic potential of Indian meal moth (Plodia interpunctella) silk extract was examined after 72 h of exposure to the SW-480 human colorectal adenocarcinoma cell line. Apoptosis was examined by monitoring the cell morphological changes by fluorescent staining, acridine orange/ethidium bromide, and DAPI, as well as by flow cytometry. The results showed that silk extract has a very good cytotoxic and proapoptotic activity. The selective effect of silk indicates the presence of a high level of biocompatibility with normal human cells. Based on the results of increased gene expression for caspase 8 and 9 in silk extract-treated cells compared to control, apoptosis was induced by a caspase-dependent pathway.